Legal Status of the Mayor of the Territorial (Local) Authority (Municipality) of Lithuania from 1990 to the Present Day - Astrauskas, Algirdas; Čelkė, Kristina; Vilkauskas, Kęstutis (International Journal of Criminology and Sociology, 2022)
Purpose of the Study: This article presents the results of a scientific study (research) of the legal status of the mayor of the territorial (local) authority (municipality) of Lithuania during the period from 1990 to the present day. Methodology: The study (research) was conducted using comparative analysis, synthesis, descriptive, graphic representation methods. Result: The results obtained during the study (research) confirm (using the example of the case of Lithuania) that the change of the legal status of the mayor of the territorial (local) authority (municipality) is a permanent process that takes place for various reasons, one of the most important of which is the change of the principle models of the structure of the territorial (local) authorities (municipalities). Novelty of the Study: The novelty of this study (research) and article is that no such study (research) has been conducted in Lithuania so far.